Analisis Tantangan dalam Implementasi Administrasi Puskesmas di Puskesmas Simalingkar - Putri Dina; Nurul Rahmawati; Sri Devi; Ira Sri Mawarni Hasibuan; Shufiah Adena Putri; Dewi Agustina (Journal on Education, 2024)
In carrying out administration at the Community Health Center, there are several challenges that can hinder the implementation of this administration. This research aims to identify and analyze the challenges faced in implementing administration at the Simalingkar Community Health Center. This research uses a qualitative approach. Data collection was carried out through in-depth interviews and observations consisting of the Head of the Community Health Center, Head of Administration, a Community Health Center employee and one of the patients using health services. The results of this discussion show that there are several challenges in implementing administration at the Simalingkar Community Health Center, including a lack of understanding of information technology, obstacles in implementing Electronic Medical Records (RME), unstable data management, and internal challenges in employee performance. By overcoming this challenge, it is hoped that the Simalingkar Community Health Center can improve the effectiveness and quality of administrative services, as well as have a positive impact on the communities served.